Political cycle, real exchange rate and aggregate supply in México - Gámez Garza, Cesáreo (2013)
This paper analyzes the relationship between the political cycle, the real exchange rate and the aggregate supply in Mexico. The period under analysis goes from 1981 to 2007, in which there were five presidential elections: 1982, 1988, 1994, 2000 and 2006. Significant evidence is found of a real appreciation of the peso, an increase in imports and an increase in the aggregate supply in the late months of each Presidential term, followed by a depreciation of the peso, a contraction of imports and a contraction in the aggregate supply in the first months of the new administration. Some conclusions and implications are discussed, as well as some lines for future research